The GASS/EUCLIPSE model intercomparison of the stratocumulus transition as observed during ASTEX: LES results. (12th August 2013) - van der, J. J.; de, S. R.; Ackerman, A. S.; Blossey, P. N.; Bretherton, C. S.; Kurowski, M. J.; Lock, A. P.; Neggers, R. A. J.; Sandu, I.; Siebesma, A. P.
<x xml:space="preserve">Abstract</x> [1] Large‐eddy simulations of a Lagrangian transition from a vertically well‐mixed stratocumulus‐topped boundary layer to a situation in which shallow cumuli penetrate an overlying layer of thin and broken stratocumulus are compared with aircraft observations collected during the Atlantic Stratocumulus Transition Experiment. Despite the complexity of the case and the long simulation period of 40 h, the six participating state‐of‐the‐art models skillfully and consistently represent the observed gradual deepening of the boundary layer, a negative buoyancy flux at the top of the subcloud layer and the development of a double‐peaked vertical velocity variance profile. The moisture flux from the subcloud to the stratocumulus cloud layer by cumulus convection exhibits a distinct diurnal cycle. During the night the moisture flux at the stratocumulus cloud base exceeds the surface evaporation flux, causing a net drying of the subcloud layer, and vice versa during daytime. The spread in the liquid water path (LWP) among the models is rather large during the first 12 h. From additional sensitivity experiments it is demonstrated that this spread is mainly attributable to differences in the parameterized precipitation rate. The LWP differences are limited through a feedback mechanism in which enhanced drizzle fluxes result in lower entrainment rates and subsequently a reduced drying at cloud top. The spread is furthermore reduced during the day as cloud layers with a greater LWP absorb more solar radiation and hence evaporate more.